Instalasi Pengolahan Air Asam dan Tambang PT Freeport Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK Air asam tam bang atau air asam batuan merupakan masalah umum ynag dihadapi oleh industri pertambangan. Pengolahannya diperlukan agar Air Asam Tambang (AAT) tidak terbuang secara bebas ke lingkungan. Sasaran utama pengolahan air asam tambang di PT. Freeport Indonesia di Irian Jaya adalah pengendalian air asam tambang agar tidak mencemari lingkungan di sam ping itu ada keuntungan yang dapat diraih sekaligus yaitu untuk mendapatkan air tambahan untuk proses dan diperolehnya katoda tembaga dari hasil proses ini. PT. Freeport Indonesia telah memiliki Instalasi Pengolah AAT yang menerapkan 2 teknologi mutakhir dalam proses pemisahan yaitu menggunakan sistem pertuk,aran ion untuk pemekatan kadar tembaga menggunakan Molecular Recognition Technology (MRT) dan proses.Electrowinning dengan teknologi ElektroMetal-Electro Winning (EMEW). Teknologi MRT telah membuktikan kemampunannya dalam pengikatan temabaga dari ARDhingga menyisakan tembaga dalam rafinatnya menjadi99.99%Cu) pada eftsiensi arus >95% dan menghasilkan larutan miskin tembaga di bawah 400 pmm adalah sesuai dengan desain awal. Masihj dijumpai permasalahan yang berkaitan dengan ketidak ajegan laju alir AAT di dalam kolom MRT. Acid rock drainage (ARD) or Acid Mine Drainage (AMD) issues are prevalent throughout world's mining industry. Acid rock drainage mangement is is needed in order to prevent its entri to ecosystem. The main objective of the ARD treatment at PT. Freeport Indonesia is to control the ARD in order to prevent polution of the surounding. There are two immediate benefits from having this ARD treatment plant firstly large volume of treated water suitable for mill consumption and seconly the production of copper cathode which can genarate revenue to mitigate the longtermcost of ARD. Recenly PT. Freeport hs commisioned it ARD treatment plant by combining two the latest technology in separation technique namely Molecular Recognition Tecgnology for extracting copper through ion exchange and ElectroMetal-Electro-Winning (EMEW) technology for recovering a salable pure copper inform of cathode product. From a technical perspective. the capability of the MRT system to remove copper in solution from ARD to very low level «10 ppm Cu) and to release the copper into loade electrolyte at reasonable tenors (3-5g/l) has been demonstrated. Similarly. the permformance of the EMEW plant to produce LMA grade A (>99.99% Cu) cathode copper at a high current efficiencies (>95%). while producing an acceptable barren electrolyte «400 ppm) is as per design criteria. Unfortunately. there are significant on going problem in maintainaing design flow rates through the packed bed MRT columns.